1969
DOI: 10.1128/jb.98.1.23-28.1969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Antitumor Agents on Growth and Glycolytic Enzymes of the Flagellate Crithidia

Abstract: Some antitumor agents known to specifically inhibit certain tumor cell enzymes were examined for activity against glycolytic enzymes and growth of the insect trypanosomatid, Crithidia fasciculata. The cytoplasmic enzymes hexokinase, a-glycerophosphate dehydrogenase, malic dehydrogenase, and glucose-6-phosphate dehydrogenase were tested. Agaricic acid (2-hydroxy-1 ,2,3-nonadecane tricarboxylic acid) was highly inhibitory (50 to 100%) to malic and a-glycerophosphate dehydrogenases at 3 x 10-5 M; 2-(p-hydroxyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The review by Wallace in 1966 (281) included a carefully worked out revision of the group but did not include a consideration of the genus Phytomonas. Since that review, there has been a renewed interest in the lower Trypanosomatidae stimulated not only by the review of Wallace, but also by the belief that these organisms might serve as models for the study of pathogens ofvertebrates and be suitable for testing effective chemotherapeutic agents (7,94,139). The pathogenic propensities of Phytomonas leptovasorum Stahel toward Coffea sp.…”
Section: Introductionmentioning
confidence: 99%
“…The review by Wallace in 1966 (281) included a carefully worked out revision of the group but did not include a consideration of the genus Phytomonas. Since that review, there has been a renewed interest in the lower Trypanosomatidae stimulated not only by the review of Wallace, but also by the belief that these organisms might serve as models for the study of pathogens ofvertebrates and be suitable for testing effective chemotherapeutic agents (7,94,139). The pathogenic propensities of Phytomonas leptovasorum Stahel toward Coffea sp.…”
Section: Introductionmentioning
confidence: 99%
“…Agaric acid is a fatty acid naturally produced by certain fungi, such as Polyporus , and can be used as anhidrotic to treat tuberculosis patients with extreme sweating ( Bacchi et al, 1969 ). Studies on Salmonella showed that the formation of biofilms was significantly inhibited after the action of agaric acid because it significantly reduced the expression of flagellar rotation genes.…”
Section: Reducing Reversible Adhesionmentioning
confidence: 99%
“…The mechanism of action is not fully understood but stems most likely from the analogy with citrate, for example, it inhibits citrate uptake in mitochondria (Chávez et al, 1978). Agaric acid is highly inhibitory against malic and α-glycerophosphate dehydrogenases at ~3.10 -5 M and it also inhibits the growth of the nonpathogenic trypanosomatid Crithidia fasciculata used as a model for the pathogenic representatives of the Trypanosoma genus (Bacchi et al, 1969). Furthermore, it inhibits ADPstimulated respiration.…”
Section: Metallodrugsmentioning
confidence: 99%